Classification of major depressive disorder using functional connectome data - Tan, Jia Jun (2019)
The brain consists of billions of neurons, communicating with each other to give humans cognitive, sensing and reasoning abilities. Major Depressive Disorder (MDD) has affects around 4% of the world population. MDD has debilitating effects on both physical and emotional health of an individual. It is important to study the brain biomarkers of the disease and develop methods to improve its diagnosis.  In recent years, there has been a rise in research related to brain state classification using data from different neuroimaging modalities. In this work, we use features obtained from fMRI scans to distinguish patients suffering from Major Depressive Disorder (MDD) and Normal control (NC).